UPAYA PENINGKATAN KEMAMPUAN MEMBACA SISWA DENGAN MEDIA BUKU CERITA BERGAMBAR PADA SISWA KELAS 1 SDN CIGOONG 3 KOTA SERANG - Saefulloh, Febri; Fajrudin, Lili; Derlis, Aprianti (Journal of Professional Elementary Education, 2025)
This research is classroom action research, which consists of several aspects of treatment and the main observation, namely improving students' reading ability with picture storybook media. The research was carried out at SDN Cigoong 3 Serang City which was registered in the 2022/2023 school year. This study uses the research design of Kemmis and Mc. Taggart, which consists of two cycles. Where each cycle consists of four stages, namely planning, implementation, observation, and reflection. The results of pre-cycle observations showed that the average level of individual absorption was only 64.97. In the 1st cycle action, the average completeness of individual absorption capacity was obtained of 70.88. In cycle 2, there was an increase with an average individual absorption completeness of 78.3. Thus, it can be concluded that learning using picture storybook media can improve the reading ability of students in grade 1 of SDN Cigoong 3 Serang City.